Reducing urea demand for rice crop through foliar application of urea in boro season - Manik, Ibrahim Hossain; Abedin, Md Anwarul; Rahman, Md Rashedur; Chakrobarty, Tusher; Jaman, Sunain Bin; Noor, Mahmud Al; Sultana, Razia (Research in Agriculture Livestock and Fisheries, 2016)
This study was carried out with a view to evaluating the effect of foliar application of urea on BRRI dhan29. The experiment was laid out in a RCBD design with seven treatments (T1 : Full dose of prilled urea @ 140 Kg N ha-1) (control), T2 (50% prilled urea + 5 foliar spray @ 0.5% N solution @ 5.5 kg N spray-1),T3 (70% prilled urea + 3 foliar spray @ 0.5% N solution @ 5.5 kg N spray-1), T4 (50% prilled urea + 3 foliar spray @ 1.0% N solution @ 11 kg N spray-1), T5 (50% prilled urea + 5 foliar spray @ 0.5% N solution @ 5.5 kg N spray-1 + 5 t ha-1 cow dung), T6 (70% prilled urea + 3 foliar spray @ 0.5% N solution @ 5.5 kg N spray-1 + 5 t ha-1 cow dung) and T7 (50% prilled urea + 3 foliar spray @ 1.0% N solution @ 11 kg N spray-1 + 5 t ha-1 cow dung) and three replications. Soil and foliar application of nitrogen significantly influenced the growth and yield contributing characters like plant height, panicle length, and effective tillers hill-1 as well as the grain and straw yields of the crop. The treatment T5 produced the highest grain yield (6.68 t ha-1) which was statistically similar to yield from T7, T6. Treatment T2,T3 and T4 gave similar yield. The grain yields of these treatments were higher than those of T1 treatment (soil application of urea only). The T5 also produced the highest straw yield of the crop. The lowest grain yield of 4.72 t ha-1 and the lowest straw yield of 5.17 t ha-1 were recorded with T1 (control). Res. Agric., Livest. Fish.3(1): 79-85, April 2016